Alignment vs rent-extraction effects of stock options. A conceptual model. Issue 4 (1st August 2016) - Catuogno, Simona; Saggese, Sara; Sarto, Fabrizia
Abstract : Purpose: We aim to develop a conceptual model that systematically interprets how key governance factors drive the alignment and the rent-extraction effects of executive stock options (hereafter SOs) as proxied by plan characteristics. Design/methodology/approach: We draw on the review of 202 articles published in international academic journals. We collect data from library databases and by hand-searching and citation-tracking relevant papers on the topic. Moreover, we review and classify the studies as related with determinants or proxies of alignment and rent-extraction effects of SOs. Findings: Our conceptual model systematically interprets the results of the literature review and identifies the relationships between archetypes, driving factors and proxies of the rent/alignment effect of executive SOs. It highlights that, given ownership archetypes, effective (ineffective) governance practices drive the alignment (rent) aim of SOs as proxied by the optimal (non-optimal) plan design. Practical implications: Our paper supports compensation committees in selecting the SO characteristics that better attract investors and retain executives. Moreover, it guides future policy making interventions aiming at mitigating the rent-extraction effect of SOs. Originality/value: The paper highlights that the governance determinants of SO aims can be effectively classified as archetypes or drivers of rent-extracting and aligning outcomes of these remuneration tools. Moreover, it offers a useful framework to guide future research efforts by providing a comprehensive interpretation of the relationships between ownership archetypes, driving factors and proxies of SO effects.